2021
DOI: 10.1111/jonm.13344
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and development of the competency inventory for Taiwanese nurse managers across all levels

Abstract: Given the increasing challenges in health care services, managerial work requires indispensable management competencies. Competent managers are one of the key contributors to effective and efficient health care service delivery (Pihlainen et al., 2016). According to the systematic review of Wong and Cummings (2007), positive nursing leadership behaviours are significantly related to patient outcomes, including increased patient satisfaction and reduced adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…However, these results raise concerns regarding the perceived importance of conceptual‐based competencies at the higher‐level of nurse managers. The competencies of the leadership domain in the NLMCI adequately represent Katz's conceptual skills, which was verified by the confirmatory factor analysis (Liou et al, 2021). Nurse managers in higher positions were expected to weight the prioritization of competencies leaning towards the leadership domain; however, the findings in this study did not reflect this anticipation.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…However, these results raise concerns regarding the perceived importance of conceptual‐based competencies at the higher‐level of nurse managers. The competencies of the leadership domain in the NLMCI adequately represent Katz's conceptual skills, which was verified by the confirmatory factor analysis (Liou et al, 2021). Nurse managers in higher positions were expected to weight the prioritization of competencies leaning towards the leadership domain; however, the findings in this study did not reflect this anticipation.…”
Section: Discussionmentioning
confidence: 75%
“…The findings also supported the study of González‐García et al (2021) which reported communication as the highest‐cited competence. In addition, several studies have reported that the ability to communicate effectively is an essential skill for nurse managers (González‐Garcia et al, 2020; Ibrahim & Ahamat, 2019; Liou et al, 2021; Yaghobian et al, 2020). The results of our present study further support the significance of effective communication in managerial competency and may imply its highly demand of training programme for the development of nurse manager.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations